Analysis of electron cyclotron emission with extended electron cyclotron forward modeling. (7th September 2018) - Denk, S S; Fischer, R; Smith, H M; Helander, P; Maj, O; Poli, E; Stober, J; Stroth, U; Suttrop, W; Westerhof, E; Willensdorfer, M
Abstract: At the ASDEX Upgrade tokamak the electron temperature ( T e ) profile is estimated from electron cyclotron emission (ECE) using radiation transport forward modeling within the integrated data analysis scheme. For the interpretation of ECE measurements in high T e > 5 keV plasmas, it was necessary to upgrade the forward model with a fully relativistic absorption coefficient including the relativistic Maxwell–Jüttner distribution. This model intrinsically enables the interpretation of ECE measurements affected by the so-called 'pseudo radial displacement' or by harmonic overlap. A numerically efficient implementation allows for the analysis of everyday ECE measurements at ASDEX Upgrade. Various ASDEX Upgrade plasma scenarios are discussed highlighting the benefits of the present radiation transport forward modeling for routine analysis.